Clinical innovation through leadership development. Issue Volume 2:Issue (2012)Supplement 1 (1st March 2012) - Coackley, Alison; Bonwick, Helen; Chapman, Laura; Wrigley, Kim; Powell, Paula; Mayland, Catriona
Abstract : Background: Senior clinicians and managers are at the forefront of innovation within Palliative Care. This places significant demands on professionals who need specific skills to maximise their effectiveness and their impact in the clinical workplace. Merseyside and Cheshire Cancer Network funded a Leadership Impact Programme for Consultants in Palliative Medicine. This links leadership style directly with engagement, wellbeing and performance which in turn helps individuals to encourage change and innovation in their organisation. Method: Diagnostic management tools, participation in a coaching centre with feedback, development workshops, and peer support. Subsequent Action Learning Sets over 12 months then facilitated participants to use their skills to produce change and innovation in their workplace. Discussion/Conclusion: The course was designed to meet the needs of the individuals and the group in general. Participants included seven senior clinicians and two senior clinical managers Evaluations were extremely positive with many specific examples of how learning and experiences from the course had impacted on clinical services across a range of organisations. 100% of participants felt the programme had met their personal objectives either very well or completely. All reported a marked improvement in strategic awareness and ability to influence. Results included enhanced team development and leadership leading to integration and improved communication; ability to deliver significant change in an organisation; sharing of new ways of tackling challenges and the commitment to collaborative ventures which were both cost effective and innovative The success of the programme has encouraged the Network to support a second 12 month course for a further cohort of senior clinicians.